Study on the laminar burning velocity of Medium-Btu syngas flame with N2 dilution based on OH-PLIF technology - Bang Wu; Ge Pu; Xun Zhang; Beibei Huang; Jiantai Du (Cogent Engineering, 2018)
The laminar burning velocity of syngas/air premixed flames was studied by Bunsen burner and OH-PLIF system. The mole fractions of nitrogen in syngas change from 0 to 50% and the equivalence ratios vary from 0.6 to 1.2 were both considered to investigate those effects on the flame speed. A new method called slope averaging method was proposed to calculate the burning velocity and two classical methods were employed to verify its accuracy. A premixed code with GRI 3.0 mechanism was adopted to predict the burning velocity as well as to expose the dominant reactions on the formation of OH and H radicals. Results show that the slope averaging method represents the equal accuracy as the surface area method and is superior to the cone angle method. In addition, the increase of N2 fractions decreases the flame speed, and the effects of N2 dilution turn weak at fuel-lean conditions. Furthermore, the dominant reactions on the formation and consumption of OH and H radicals are inhibited as XN2 increases.